2015
DOI: 10.1111/hpb.12474
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous hepatic haemorrhage: a review of pathogenesis, aetiology and treatment

Abstract: A spontaneous hepatic haemorrhage is an acute presentation of a spectrum of conditions that requires early diagnosis and multidisciplinary management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 61 publications
1
50
0
5
Order By: Relevance
“…More importantly regression of fibrosis associated with ant-viral therapy is associated with improved liver function. 2,8,9 Spontaneous hemorrhage from the liver occurs evenly from benign or malignant causes, one-third of which are primary liver disease. If the patients presents emergently, angiographic embolization may control the bleeding and allow for elective resection once the sequelae of bleeding have resolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly regression of fibrosis associated with ant-viral therapy is associated with improved liver function. 2,8,9 Spontaneous hemorrhage from the liver occurs evenly from benign or malignant causes, one-third of which are primary liver disease. If the patients presents emergently, angiographic embolization may control the bleeding and allow for elective resection once the sequelae of bleeding have resolved.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these issues, SHH has never been comprehensively reviewed possibly because of its rarity, the potentially wide range of underlying conditions. 2,3 A diagnosis of SHH is based on a clinical index of suspicion in patients with a known underlying condition. However, this is not always as straightforward as SHH is a rare complication in patients with connective tissue disease.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor size and location, particularly in HCC, do not seem to correlate with the risk of bleeding, as both large, central lesions and small, peripheral lesions have an approximately equal propensity to bleed. 32 The hemorrhage may not even come from the tumor itself; some have suggested that tumoral growth may fracture adjacent liver parenchyma and breach Glisson's capsule from within, thus leading to bleeding. 31 A recent history of blunt trauma may be elicited from patients as the inciting event.…”
Section: Livermentioning
confidence: 99%
“…Based on the unique feature of imaging, it could be speculated for differential diagnosis that there was intratumoral hemorrhage that was detected as heterogeneously high-intensity regions in the hepatocellular phase of Gd-EOB-DTPA contrast-enhanced MRI. Several types of tumors are known to show hemorrhage in the mass, such as HCC [15] , HCA [16] , metastatic tumors of lung and renal cancers [17] , and angiomyolipoma (AML) [18] . In the present patient, imaging studies revealed no findings of metastatic liver tumor or AML; neither metastatic liver tumor nor AML show any enhancement on Gd-EOB-DTPA in the hepatocellular phase on contrast-enhanced MRI.…”
Section: Hcamentioning
confidence: 99%